Is Peru Prepared for Large-Scale Sustainable Rural Electrification? - Cordero-Carrasco, R; Christin-Feron, S (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Peru has historically been among the Latin-American countries with a low rural electrification rate. Aiming to improve this situation, the country conducted several electrification efforts in the last few decades that included off-grid photovoltaic (PV) solutions for remote areas (where the grid expansion was unviable). More recently, the government has also sponsored a massive program that aims to deploy a minimum of 150,000 off-grid PV solutions in the upcoming years. In this paper, we assess the sustainability of rural electrification programs in Peru, paying special attention to the ongoing "massive program". Our assessment considers four dimensions of sustainability (institutional, economic, environmental, and socio-cultural) and is based on an exhaustive qualitative document analysis complemented by semi-structured expert interviews. We found that the lack of strong formal institutions with a flexible and decentralized structure seriously compromises the sustainability of rural electrification efforts in Peru. Staff rotation and overlapping competences have caused disturbing changes and inhibited following a strategic line, while widespread outsourcing combined with weak controls have often affected the reliability of the deployed systems. Although cross subsidies have made off-grid PV systems affordable for users, systems often fell short of energy demand. Notably, we found that Peruvian officials appear to be unaware of the importance of local participation, and there is a significant mistrust between the government and the rural population (especially in areas where mining is extensive). As a consequence, most of the projects are still designed without the participation and engagement of the communities, which has frequently led to project failures, payment defaults, and inhibited seizing opportunities regarding productive uses of off-grid PV systems. We expect that our findings may help Peruvian institutions to address the most severe drawbacks affecting their rural electrification efforts based on off-grid PV systems. © 2018 by the authors.